Lettering, Karfule - Ghosh, Ayan (2023)
Karfule is word-play on 'Car Fuel'. The pump opened in 1938 and is run by the Sequeira family, now in its third generation. The business was started by Gabriel Sequeira, who had immigrated from Goa in the late 1920s. Until his death in 2001, at 98 years of age, Gabriel Sequeira remained actively involved in the Karfule business, visiting the pump regularly.